The effectiveness of neuro-music therapy according to the Heidelberg model compared to a single session of educational counseling as treatment for tinnitus: A controlled trial - Argstatter, Heike; Grapp, Miriam; Hutter, Elisabeth; Plinkert, Peter K.; Bolay, Hans Volker (Journal of psychosomatic research, 2015)
Objectives - Tinnitus is a very common symptom, yet the quest for an effective treatment is challenging. Results from several clinical trials support the notion that neuro-music therapy is an effective means to reduce tinnitus distress with short duration and long lasting effect. However, until now, the effectiveness has not been tested in a controlled trial against an active comparator. - Methods - The trial was designed as two-center, parallel intervention group controlled study with two intervention groups: Counseling (50minute individualized personal instruction) or neuro-music therapy (counseling plus eight 50-minute sessions of individualized music therapy). Data of n=290 patients suffering from chronic tinnitus were analyzed. Outcome measure was the change in Tinnitus Questionnaire Total Scores (TQ) from baseline (admission) to end of treatment. - Results - Both treatment groups achieved a statistically relevant reduction in TQ scores, though 66% of patients in the music therapy group attained a clinically meaningful improvement compared to 33% in the counseling group. A binary logistic regression revealed two variables significantly influencing therapy outcome: initial tinnitus score and type of therapy with an OR for the music therapy compared to the counseling of 4.34 (CI 2.33-8.09). - Conclusions - Counseling is an appropriate treatment option with well above chance of improvement. The neuro-music therapy outperformed the counseling. This treatment targets the tinnitus sound itself, is short in duration, intrinsically motivating and easy to operate and thus presents a possible complement to the therapeutic spectrum in chronic tinnitus. The trial was registered at the ClinicalTrials.gov registry (ID: NCT01845155).